2022
DOI: 10.1021/acs.inorgchem.2c02885
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Oxidation-Induced Size Conversion of [Au6(dppp)4]2+ to [Au8(dppp)4Cl2]2+

Abstract: Oxidation-induced conversion of gold nanoclusters is an important strategy for preparing novel atomically precise clusters and elucidating the kinetic correlations of different clusters. Herein, the oxidation-induced growth from [Au 6 (dppp) 4 ] 2+ to [Au 8 (dppp) 4 Cl 2 ] 2+ (reported by Konishi and co-workers) has been studied by density functional theory calculations. A successive oxidation → Cl − coordination → oxidation → Cl − coordination sequence occurs first to activate the Au 6 structure, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…While calculating DFT, the oxidation-induced growth from Au 6 to Au 8 -1 was studied, and the results show the following sequence of successive oxidation → Cl – coordination → oxidation → Cl – coordination, which activates the Au 6 structure. This process leads to the high bond cleavage activity of Au core –Au corner and the subsequent formation of [Au 2 (dppp) 2 Cl] + and [Au 4 (dppp) 2 Cl] + fragments . Then two Au 4 fragments dimerize, and the diphosphine coordination rearranges to form the thermodynamically stable Au 8 -1 .…”
Section: Chemical Inducements-triggered Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…While calculating DFT, the oxidation-induced growth from Au 6 to Au 8 -1 was studied, and the results show the following sequence of successive oxidation → Cl – coordination → oxidation → Cl – coordination, which activates the Au 6 structure. This process leads to the high bond cleavage activity of Au core –Au corner and the subsequent formation of [Au 2 (dppp) 2 Cl] + and [Au 4 (dppp) 2 Cl] + fragments . Then two Au 4 fragments dimerize, and the diphosphine coordination rearranges to form the thermodynamically stable Au 8 -1 .…”
Section: Chemical Inducements-triggered Reactionsmentioning
confidence: 99%
“…However, due to the distinctly physical-chemical properties (e.g., the steric hindrance, ,,,, electron-withdrawing/donating, and hydrophobicity and hydrophilicity , ) of different groups of inducers, the original structures may not be the most stable state, and then the structural transformation takes place. (iii) The redox process of clusters is accompanied by reduction and increase of NC electrons, which can cause significant changes in the cluster geometry, in particular, the change of the electronic structure of superatom NCs will induce the structural transformation to a more stable configuration (refs , , , , and ). (iv) The inducer does not directly react with the cluster, only changes the physical-chemical environment of the cluster, such as solvent polarity, pH, temperature, light, electric field, and external pressure. ,,, …”
Section: Summary and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuing our recent endeavors to understand the kinetic profiles of the cluster conversion reactions, herein we explored the reaction and especially the kinetic profiles of the reaction of [Au 23 (CHT) 16 ] − with HSAdm. It was found that during the 16 h conversion of [Au 23 (CHT) 16 ] − to Au 16 (SR) 12 , Au 21 represents a pivotal intermediate state.…”
mentioning
confidence: 99%